PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM LEMBAGA PENDIDIKAN - FAHMIAH AKILAH (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2018)
Abstract: One of the most critical resources in management is human resources. The importance of this human resource requires being apprehended by all levels of management, as well as in management education. Although the emergence of sophisticated technology today, the human factor still strikes an essential role in the success of an association. Human resources are an indispensable constituent in an organisation because humans are the first and primary element in management before the other aspects. Accordingly, human resource management has a vital role in administering and accomplishing organizational goals, not least in educational institutions. Human resources must be appropriately regulated by its function so that these human resources can execute a role in the duties and functions of the institutions that they involve. Keywords: Human Resources, Educational Institution